Performance Measurement in the Internal Audit Departments in Poland - the State of the Art and Prospects for Development - Bednarek, Piotr (Olsztyn Economic Journal, 2014)
The paper reports the major results of a study of performance measurement of internal auditing in various organizations operating in Poland in 2013 and prospects for development. The research implies that many internal audit departments formally do not measure performance, while others do measure, but only informally. Many times satisfaction indicators of key internal audit stakeholders are not identified, the information on performance is not reported to anyone apart from the internal audit staff, and the information is not used for continues improvement. The most often used performance measures in practice are focused on measuring effectiveness of audit processes and impact of internal audit services on organizations' performance. In addition there are internal audit efficiency and output measured. Quality measures are less common. Stakeholders, scope and usage of performance measurement are related to various organizational characteristics. Many respondents have declared that in future will start and formalize performance measurement and based on it they will improve internal audit performance. In future performance measurement will be more focused on internal audit quality and value added.